ASSESSMENT OF PRINCIPALS’ GOAL SETTING APPRAISAL PRACTICES ON STUDENTS PERFORMANCE AT KENYA CERTIFICATE OF SECONDARY EXAMINATION IN PUBLIC SCHOOLS IN KIMININI SUB-COUNTY, KENYA - Mbovi, Wafula Medarn; Barasa, Lukoba Newton; Kikechi , Ronald Werunga (IJRDO- Journal of Educational Research, 2023)
This study aimed to carry out the assessment of principals’ goal setting appraisal practices on students’ performance at KCSE in public secondary schools in Kiminini Sub-County, Kenya. It anchored its study on Goal Setting Theory of Motivation by (Locke, 1990), which asserts that setting clear, demanding goals and receiving helpful feedback results in increased task performance. Using simple random sampling technique, 18 principals and 18 deputy principals, 24 Heads of Departments and 150 teachers were selected as a sample from 60 schools in Kiminini Sub County. Information from the principals was gathered using a purposeful sampling method. In order to evaluate the Principal's Evaluation procedures, interview schedule was conducted, whereas from Deputy Principals, Heads of Departments and teachers, questionnaires were employed. Linear regression, ANOVA and correlations besides descriptive statistics between the academic performance of the instructors and the principals' goal setting appraisal processes was used to analyze the study's variables. Presentation of the analyzed data was done by use of tables, charts, figures and thematically. Data was interpreted to ascertain if there existed a positive and significant relationship between Principal’s goal setting Appraisal practices and the students’ performance in the respective KCSE mean scores in public secondary schools in Kiminini Sub County. The study then concluded that Principals goal setting appraisal practices in Public Secondary Schools significantly affected Student performance in KCS E.